## Filters

Clear All
adding the following terms we will get Subtracting  We will get
Adding   Will give the result as follows Subtracting  Will give the result as follows
Monomial: a, xy, 7 binomial: a+b, xy+5, 4mn+7 Trinomial: ab+a+b, 5x2-x+2, 4pq-3q+5p, 4m-7n+10 Polynomial with 4 terms: ab+a+b-5
The like terms are grouped below Group 1: , ,  Group 2: , ,  Group 3: , ,
i)  has two terms 4x and -3y the coefficient of x is 4 and the coefficient of y is -3 ii) a+b+5 has 3 terms a,b and a constant that is 5. the coefficient of a is 1 and b is also 1. Constant terms have no coefficient  iii) 2y+5 has two terms 2y and 5 which is constant.  The coefficient of y is 2. Constant terms have no coefficient  iv) 2xy has only one term which is 2xy and the coefficient of xy is 2
We can write as many expressions we need with 4 terms. Following are a few examples of expression with 4 terms
The terms in the expression are        is obtained by adding the product of 8 and y with the product of 3 x and x the tree diagram for the expression is given below  has two terms 7mn and 4 and the expression is obtained by subtracting 4 from the product of 7,m and n. The tree diagram is shown below.  has only one term, that is the expression itself. The expression is formed by multiplying...
the above expression is obtained by adding 7xy with 5. Here 7xy is obtained by multiplying 7,x and y   the above expression is obtained by subtracting the product of 5 and x from the product of 4,x and x
Below you can find the table of number patterns:
The number of segments required to form n of each digits shown above are 5n + 1, 3n + 1 and 5n + 2 When n = 5 When n = 10 When n = 100
When a = 5 and b = -3 the value 2( a2 + ab ) + 3 - ab = 38
Therefore for a = -5 when the value of x=0
If p = -10 the value of p2 - 2p - 100 = 20
If z = 10 the value of z3 - 3( z - 10 ) = 1000
The expression is simplified as follows and also obtained their values (i) (ii) (iii) (iv) (v)
If x is equal to 2 the value of 4( 2x - 1 ) + 3x + 11 = 29
If x is equal to 2 the value of  6x + 5( x - 2 ) = 12
If x is equal to 2 the value of 3( x + 2 ) + 5x - 7 = 15
If x is equal to 2 the value of x + 7 + 4( x - 5 ) = -3

0+0×-1+2=-1+2=1

Exams
Articles
Questions